Monetisasi Data, Sentralisasi QRIS, dan Tantangan Integrasi Nilai Syariah dalam Sistem Pembayaran Digital Indonesia: (Data Monetization, QRIS Centralization, and the Challenge of Sharia Value Integration in Indonesia's Digital Payment System) - Zainal Fanani; Bustanul Arifin; Fadwa Aly Elsayed Mohamed (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2025)
Abstract: This study addresses key issues regarding data monetization, system centralization, and digital payment platform designs that may conflict with maqashid sharia principles such as justice ('adl), public benefit (maslahah), and protection from systemic harm (dlarar). The digital payment transformation in Indonesia through QRIS and digital rupiah has highlighted the dominance of the state and corporations in financial transaction infrastructures. This centralization raises ethical concerns that need to be examined within the framework of digital political economy and Sharia ethics. Using a qualitative approach, we critically analyze national policies, regulatory documents (e.g., PADG and BSPI 2025), and contemporary fiqh literature. The findings reveal that Indonesia's digital payment system lacks substantive integration with Sharia ethics, posing risks in access to justice, data ownership (milkiyah al-ma'lumat), and infrastructure monopoly. We recommend a